Biological basis of “depression with liver-qi stagnation and spleen deficiency syndrome”: A digital gene expression profiling study - Junling Li (Journal of Traditional Chinese Medical Sciences, 2015)
Objective: To investigate the biological basis of “depression with liver-qi stagnation and spleen deficiency syndrome”. Methods: A digital gene expression profiling method was conducted to explore global changes in the mRNA transcriptome in a rat model of depression with liver-qi stagnation and spleen deficiency syndrome. Real-time quantitative polymerase chain reaction (q-PCR) was performed to verify the five genes most interest based on the Kyoto Encyclopedia of Genes and Genome (KEGG) analysis. Sini San, which disperses stagnated liver qi and strengthens the spleen, was administered to the model rats to observe whether it could reverse these genetic changes in the liver. Results: Forty-six differentially expressed genes were identified. Three of the five genes of most interest—Hnf4α, Hnf4γ and Cyp1a1—based on KEGG analysis, were confirmed by real-time q-PCR. Sini San reduced the gene expression changes of Hnf4α, Hnf4γ and Cyp1a1 in the rat model. Conclusions: Hnf4α, Hnf4γ and Cyp1a1 are involved in “depression with liver-qi stagnation and spleen deficiency syndrome”. These findings indicate that depressed rats with liver-qi stagnation and spleen deficiency syndrome are at risk of liver diseases. Furthermore, our results will inform exploration of the etiology of depression and help in the development of effective therapeutic strategies.